The health related quality of life trajectory in patients after percutaneous coronary intervention - Fernandez, R.; Davidson, Patricia; Salamonson, Y.; Griffiths, R.; Juergens, C. (Lippincott Williams & Wilkins, 2007)
PURPOSE: The purpose of this study was to describe the trajectory of cardiac patient’s perceptions of health-related quality of life (HRQoL) during a 24-month period in a community-based population. METHODS: After obtaining informed consent, a self-administered questionnaire was mailed to participants. Using the MacNew questionnaire, which assesses the emotional, physical, social, and global domains, HRQoL outcomes were assessed. RESULTS: Completed questionnaires were received from 202 participants (75%). Improvements in the emotional, physical, social, and global HRQoL scores were observed until 15 to 17 months after the index percutaneous coronary intervention, after which a decline was observed. However, the scores in all HRQoL domains remained high when compared with the scores at 12 months. No clinical or sociodemographic predictors for HRQoL were identified. CONCLUSIONS: The information obtained from this study will enable clinicians to further understand the process of recovery and adjustment of patients after percutaneous coronary intervention and the development of tailored strategies for patient management.